A219 AMINOTRANSFERASE IMPROVEMENTS IN PATIENTS WITH NON-ALCOHOLIC STEATOHEPATITIS ARE ASSOCIATED WITH FIBROSIS REGRESSION IN THE REGENERATE STUDY. (21st February 2022) - Ramji, A; Rinella, M; Dufour, J; Anstee, Q M; Younossi, Z; Loomba, R; Sanyal, A J; Capozza, T; Trylesinki, A; Ratziu, V
Abstract: Background: The interim analysis of the REGENERATE study showed obeticholic acid (OCA) 25 mg treatment significantly improved liver histology in patients with nonalcoholic steatohepatitis (NASH) and fibrosis. Elevations in aminotransferases are associated with adverse liver-related outcomes in NASH. Aims: Here, we evaluate the utility of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) as markers of treatment response to OCA in patients with NASH. Methods: Changes in ALT (upper limit of normal [ULN] = 55 U/L) and AST (ULN = 34 U/L) were assessed systematically at 1, 3, 6, 12, and 18 months in 931 NASH patients with stage 2 or 3 fibrosis randomized 1:1:1 to placebo (PBO), OCA 10 mg, or OCA 25 mg in REGENERATE (intent-to-treat population). Least-square mean (LSM) and 95% confidence intervals (CIs) of percentage change from baseline in ALT and AST were analyzed using a mixed-effect repeated-measures model. Results: Baseline characteristics were well-balanced across treatment arms: ALT 79±53 U/L; AST 58±36 U/L; 44% F2, 56% F3. Aminotransferase values were > ULN for ALT in 60% (7% > 3xULN), and for AST in 74% (9% > 3xULN) of patients. Rapid, progressive, and dose-dependent improvement in ALT and AST was seen across PBO, OCA 10 mg, and OCA 25 mg arms, which at Month 18 was: ALT LSM change (95% CI), respectively, -4.9% (-10.7–0.9), -23.2% (-28.9– -17.4) and -31.9% (-37.7– -26.1) and in AST, -8.7% (-12.1– -5.2), -13.4% (-16.8– -9.9), and -19.4 (-22.8– -15.9). ALT and AST LSM reductions in OCA arms vs PBO were seen regardless of patient ULN status at baseline. In all patients, ALT/AST reduction was associated with probability of fibrosis regression at Month 18, ranging from approximately 20%, 95% CI (14–27) to 45% (37–54) with any reduction in ALT (> 0%–100%) and between approximately 20%, 95% CI (25–38) to 43% (35–57) with any reduction in AST (> 0%–100%). Interestingly, even with increases of ≤ 40% in AST or ALT there was still a small probability of fibrosis regression (< 20%). Analysis of changes in ALT and AST in individual patients showed that more patients had improvements on OCA than PBO at Month 18 (FIG 1). Conclusions: OCA resulted in consistent dose-dependent improvement of ALT and AST. Patients with reductions in ALT or AST were up to twice as likely to have fibrosis improvement than those whose ALT or AST increased. The REGENERATE study is ongoing and will continue through clinical outcomes for verification and description of clinical benefits of OCA in treatment of NASH. Funding Agencies: None